Using electricity options to hedge against financial risks of power producers - Salvador Pineda; Antonio J. Conejo (Journal of Modern Power Systems and Clean Energy, 2013)
As a consequence of competition in electricity markets, a wide variety of financial derivatives have emerged to allow market agents to hedge against risks. Electricity options and forward contracts constitute adequate instruments to manage the financial risks pertaining to price volatility or unexpected unit failures faced by power producers. A multi-stage stochastic model is described in this tutorial paper to determine the optimal forward and option contracting decisions for a risk-averse power producer. The key features of electricity options to reduce both price and availability risks are illustrated by using two examples.